Studi Kasus Hubungan Supportive Leadership, Work Engagement dan Dominansi Otak TNI Satuan JASDAM XIV/HSN - Arifatah Achmad Rahmawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research examines subordinates' perceptions of supportive leadership relationships and the work engagement of TNI personnel. The research methods used in this research are quantitative and qualitative, with a cross-section research design. In this study, respondents consisting of 35 TNI personnel and one leader in the Jasdam XIV/HSN unit, which was the case study, were asked to fill out a supportive leadership & work engagement questionnaire, fingerprint testing using PRIADI Psychological Fingerprints and interviews as a medium for qualitative observation. The results show a positive relationship between supportive leadership & work engagement with an R2 (influence) value of 16.7%. Apart from that, the test results using PRiADI Psychological Fingerprints show that the leader's brain dominance is top left (analytical brain), the supportive leadership style has been implemented optimally by the leader as shown by giving rewards in the form of (attention, motivation, and encouragement) to subordinates. This can increase work engagement among TNI personnel from the Jasdam XIV/HSN unit, which is confirmed by the results of PRiADI Psychological Fingerprints and qualitative observations. In conclusion, supportive leadership can increase the work engagement of TNI personnel to improve the TNI's credibility in maintaining Indonesia's unity and integrity. Keywords: supportive leadership, work engagement, PRiADI Psychological Fingerprints, TNI